Towards a Better Understanding of the Incremental Capital-Output Ratio - Vanek, J.; Studenmund, A. H. (Quarterly Journal of Economics, 1968)
Introduction, 452. — I. Theoretical considerations, 454. — II. Estimating the relation between the rate of growth and the gross incremental capitaloutput ratio, 455. III. Other factors affecting ky 456. — IV. Conclusions, comments, hypotheses, 459. — Appendix, 463.